UMP listed among the top 751–800 universities worldwide - Hazlina, Faizal; Mimi Rabita, Abdul Wahit (2020)
Pekan, 10 June 2020 - Universiti Malaysia Pahang (UMP) maintains its position grouped in the 751–800th best worldwide after being listed in the QS World University Rankings (QS-WUR) 2021 that was recently announced by the international ranking agency QS Quacquarelli Symonds.